THE USE OF STORYTELLING TO ATTRACT STUDENTS INTEREST THESIS - Afifa Afifa (The Ellite of Unira, 2023)
The teacher has an important role in the teaching and learning process, besides that the teacher also has responsibility for children's development starting from morals, principles, creativity and children's motor actions. The author has conducted research on 50 respondents or 50 students who are in high school in Az Zubair, Pamekasan. Of the 50 respondents, the researcher can determine the number of likerts according to the research title that the researcher took. Of the 50 respondents the researcher concluded that as many as 31% of students liked and accepted English using the storytelling method.